2020
DOI: 10.26434/chemrxiv.11897157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Azetidinimines as a Novel Series of Non-Covalent Broad-Spectrum Inhibitors of β-Lactamases with Submicromolar Activities Against Carbapenemases of Classes A, B and D

Abstract: The increasingly worrisome situation of antimicrobial resistances has pushed synthetic chemists to design original molecules that can fight these resistances. To do so, inhibiting β-lactamases, one of the main modes of resistance to β-lactam antibiotics, is one of the most sought-after strategies, as recently evidenced by the development and approval of avibactam, relabactam and vaborbactam. Yet molecules able to inhibit simultaneously β-lactamases belonging to different molecular classes remain scarce and cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This reaction, named the Staudinger synthesis, set the template for accessing this particular heterocycle and inspired a myriad of synthetic variations [2] . Our group developed an imino‐variant of this transformation by using an ynamide [3–10] ( 1 a ) to generate in situ [11,12] a highly reactive ketenimine ( 2 a ) [13–15] which can engage in a [2+2] cycloaddition with a diaryl imine ( 3 a ) to give an azetidinimine (Scheme 1a) [16,17] . Exploring this transformation further, we found that when the same reaction conditions were applied to the homologous benzylimine 3 b , the formation of the expected azetidinimine was not observed.…”
Section: Methodsmentioning
confidence: 99%
“…This reaction, named the Staudinger synthesis, set the template for accessing this particular heterocycle and inspired a myriad of synthetic variations [2] . Our group developed an imino‐variant of this transformation by using an ynamide [3–10] ( 1 a ) to generate in situ [11,12] a highly reactive ketenimine ( 2 a ) [13–15] which can engage in a [2+2] cycloaddition with a diaryl imine ( 3 a ) to give an azetidinimine (Scheme 1a) [16,17] . Exploring this transformation further, we found that when the same reaction conditions were applied to the homologous benzylimine 3 b , the formation of the expected azetidinimine was not observed.…”
Section: Methodsmentioning
confidence: 99%